The Design of Flexible Telemedicine Framework for Healthcare Big Data - Khanapi Abd Ghani, Mohd; Abed Mohamed, Mazin; A Mostafa, Salama; Mustapha, Aida; Aman, Hannani; Musa Jaber, Mustafa (International Journal of Engineering and Technology, 2018)
The lifetime health record, which correlates each episode of care of an individual into a continuous health record, is the central key delivery of the Malaysian integrated telehealth application. A lifetime health record for an individual is the integration on his/her life timeline of all his/her electronic health records from healthcare centers he/she has been to since birth. The electronic medical records to be collected that form the lifetime health record, can be gathered from various spectrums of health information systems and healthcare levels, implying the necessity to handle diverse communications and information technology infrastructures. Most important consideration, however, is that the lifetime health record should contain not only longitudinal health summary information, but also the possibility of on-line retrieval of all patient health history whenever required, even during computer system downtime and unavailability of landline telecommunication network. It is only with such comprehensiveness of health records that the risk of inappropriate delivery of care may be reduced, and most of all the true continuum of care may be achieved.Â This paper develops an interoperable framework for an integrated and distributed telemedicine system in Malaysia, intended to cope with these requirements.Â The overview on the framework is provided, followed by a concise description of the three major components of the framework.Â